Cardiopulmonary transplantation. Issue 5 (May 2021) - Parizkova, Barbora; Wright, Gavin
Abstract: The Registry of the International Society for Heart and Lung Transplantation reported 108, 034 adult recipients of deceased donor heart transplants between January 1992 and June 2018. The 37th annual adult lung transplant report submitted data to the ISHLT TTX Registry on 67, 493 adult recipients of deceased donor transplants between January 1, 1992 and June 30, 2018. In recent years more than 5000 heart transplants and approximately 4000 lung transplants have been performed annually across 388 centres worldwide. Heart transplantation is a proven surgical option for selected patients with advanced heart failure refractory to surgical or medical management. Lung transplantation is the definitive treatment for end-stage lung disease in patients who have failed medical therapy. More than 90% of adult patients presenting for heart transplantation have dilated cardiomyopathy or ischaemic cardiomyopathy. Anaesthetic principles for heart transplantation comprise full monitoring, including transoesophageal echocardiography, cardiostable anaesthesia and cardiac support with assessment and treatment of pulmonary vascular hypertension. Median survival after cardiac transplantation is 11.9 years. Lung transplantation includes single-lung, double-lung, bilateral sequential single-lung, heart–lung and lobar transplantation. The most common indication, representing more than one-third of all transplant recipients, is chronic obstructive pulmonary disease. Donor criteria have become more liberal and lung transplants may involve cardiopulmonary bypass. Pre-bypass air trapping can compromise cardiac function. Postoperative ventilation management should be guided by pH, not P a CO2 . Thoracic epidural analgesia provides optimal pain relief without respiratory depression. Five-year survival after lung transplantation is approximately 65%.